2021
DOI: 10.1111/jac.12563
|View full text |Cite
|
Sign up to set email alerts
|

Shading under drought stress during grain filling attenuates photosynthesis, grain yield and quality of winter wheat in the Loess Plateau of China

Abstract: In the Loess Plateau region of China, winter wheat often undergoes prolonged cloudy days without rain which may affect the grain yield and quality. This study examined the impacts of shading and drought conditions during the grain‐filling period of winter wheat (Triticum aestivum L.) on photosynthesis, grain yield and quality traits in a greenhouse experiment. The imposed shading and irrigation‐deficit treatments were corresponded with naturally cloudy weather in the rainfed area. Five shading treatments, 15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Similarly, during the blended growth period, increased height of wheat crop may have caused the shading effect for the companion crop. A significant reduction in chlorophyll content of maize crop due to shading has been well reported in previous study ( Naseer et al., 2022 ). Similarly, Pang et al.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, during the blended growth period, increased height of wheat crop may have caused the shading effect for the companion crop. A significant reduction in chlorophyll content of maize crop due to shading has been well reported in previous study ( Naseer et al., 2022 ). Similarly, Pang et al.…”
Section: Discussionsupporting
confidence: 83%
“…The authors explained this phenomenon in terms of the impact of water stress on the number of grains per spike, and suggested that crops can be protected from water stress during these two periods to maximize the probability of good harvests (Huang et al, 2020). Such remote sensing-based conclusions were also supported by a recent experimental study conducted at a site in the LP in which the authors observed modulations of winter wheat yield by drought stress during LG (Naseer et al, 2022). Taking all of these results together, we recommend that winter wheat should be protected from water stress mainly during MG and LG by rationally allocating the input of water and fertilizer in order to maximize the probability of a good harvest.…”
Section: Effect Of Drought On Winter Wheat Yieldmentioning
confidence: 76%
“…Under drought-induced oxidative stress, plants show abnormalities in physiological and biochemical processes leading to cell death [16]. Photosynthesis is one of the most sensitive processes to drought stress [17,18] because drought damages the photosynthetic process and causes the stomatal closure. The reduced photosynthesis due to stomatal closure is reported to limit the supply of CO 2 [18].…”
Section: Introductionmentioning
confidence: 99%